MEMAHAMI BAGAIMANA SEORANG ANAK BERKEMBANG DAN BELAJAR - Nirwana, Evi Selva; Afrilioni, Yonanda; Fitri, Annisa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article aims to: (1) identify developmentally appropriate classrooms; (2) describe key perspectives on early childhood learning and development; and (3) recognize similarities and differences in child development. Classrooms designed based on child development principles have proven to be an important foundation in creating safe, supportive and stimulating learning environments. Early childhood educators need to understand the physical and psychological dimensions of an ideal learning space, including the layout, props and social interactions that occur within it. In addition, an understanding of child development theories such as those of Piaget, Vygotsky and Erikson is an important foundation in designing holistic learning approaches. Recognizing that each child develops at a different pace and learning style, teachers are expected to be able to respond adaptively to children's individual needs. Thus, the quality of early childhood education will improve significantly, as learning activities are designed according to the developmental characteristics of children from infancy to 8 years of age.